Relasi Murshid dan Murid dalam Bimbingan Tarekat ShÄdhilÄ«yah di Pesulukan Thoriqot Agung Tulungagung - Musthofa, Chabib (Program Studi Filsafat Agama Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2017)
This article attempts to reveal the relation of murshid and mur?d (pupil) of the Tarekat Sh?dhil?yah at Pesulukan Thoriqot Agung (PETA) in Tulungagung East Java. The author discusses the pattern of constructive relation between murshid and his pupils to build an objective social reality of the tarekat in terms of its teaching and ritual aspects. This moment subsequently becomes a medium of adaptation of the pupils. It helps the pupils to reach the process of spiritual happiness and internalize it into his/her consciousness and behaviors. Within such relation, social construction affirms that community is a result of human?s production and it stands beyond the zone of an external phenomenon. This external phenomenon consists of material and non-material subjects. In time, the external phenomenon becomes an objective reality, which forms understanding and behavior of other people in other different periods. Murshid has been the main subject within a tarekat who is capable to color spiritual realm of his pupils. The plot of murabb? al-r?? (spiritual educator) attached upon murshid is not a mysteriously hidden, abstract, and unseen epithet. Instead, this spiritual status is applied in his social action and behavior and it colors the spiritual actions of his mur?d.